Exploring of the ameliorative effects of Nerium (Nerium oleander L.) ethanolic flower extract in streptozotocin induced diabetic rats via biochemical, histological and molecular aspects - Battal, Abdulhamit; Dogan, Abdulahad; Uyar, Ahmet; Demir, Abdulbaki; Keleş, Ömer Faruk; Celik, Ismail; Baloglu, Mehmet Cengiz; Aslan, Ali (Springer Science and Business Media LLC, 2023)
Nerium oleander L. is ethnopharmacologically used for diabetes. Our aim was to investigate the ameliorative effects of ethanolic Nerium flower extract (NFE) in STZ-induced diabetic rats.Seven random groups including control group, NFE group (50 mg/kg), diabetic group, glibenclamide group and NFE treated groups (25 mg/kg, 75 mg/kg, and 225 mg/kg) were composed of forty-nine rats. Blood glucose level, glycated hemoglobin (HbA1c), insulin level, liver damage parameters and lipid profile parameters were investigated. Antioxidant defense system enzyme activities and reduced glutathione (GSH) and malondialdehyde (MDA) contents and immunotoxic and neurotoxic parameters were determined in liver tissue. Additionally, the ameliorative effects of NFE were histopathologically examined in liver. mRNA levels of SLC2A2 gene encoding glucose transporter 2 protein were measured by quantitative real time PCR.NFE caused decrease in glucose level and HbA1c and increase in insulin and C-peptide levels. Additionally, NFE improved liver damage biomarkers and lipid profile parameters in serum. Moreover, lipid peroxidation was prevented and antioxidant enzyme activities in liver were regulated by NFE treatment. Furthermore, anti-immunotoxic and anti-neurotoxic effects of NFE were determined in liver tissue of diabetic rats. Histopathogically, significant liver damages were observed in the diabetic rats. Histopathological changes were decreased partially in the 225 mg/kg NFE treated group. SLC2A2 gene expression in liver of diabetic rats significantly reduced compared to healthy rats and NFE treatment (25 mg/kg) caused increase in gene expression.Flower extract of Nerium plant may have an antidiabetic potential due to its high phytochemical content.
Keywords: Glycated Hemoglobin; Blood Glucose; Plant Extracts; Flowers; Lipids; Antioxidants; Streptozocin; Rats; Diabetes Mellitus, Experimental; Liver; Animals; Hypoglycemic Agents; Insulin; Nerium; 3. Good health